2024 ACM A.M. Turing Award - Gams, Matjaž (Informatica (Ljubljana), 2025)
The 2024 ACM A.M. Turing Award (the “Nobel Prize of Computing”) was awarded to Andrew G. Barto and Richard S. Sutton “for developing the conceptual and algorithmic foundations of reinforcement learning.” Announced on 5 March 2025, the honor not only celebrates nearly five decades of pioneering scholarship but also signals that reinforcement learning (RL) has moved from the periphery of artificial-intelligence research to its very center —most visibly through its role in training large-language models (LLMs).
Keywords: award; large-language models; Nagrade, priznanja ipd.; Računalništvo; Strojno učenje